Komitmen Afektif pada Pegawai Sektor Publik: Pengaruh Percaya Diri, Kompetensi Profesional, dan Motivasi Kerja: Affective Commitment among Public Employees: The Impact of Self-Confidence, Professional Competence, and Work Motivation - Ilasniati Ilasniati; Afriyeni Afriyeni (Al Dzahab, 2025)
Purpose: This study aims to examine the influence of self-confidence, professional competence, and work motivation on the affective commitment of public sector employees at the Regional Secretariat of Kerinci Regency, Indonesia. Design/Methodology/Approach: This study employed a quantitative research design involving employees of the Regional Secretariat of Kerinci Regency as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS software. Findings: The findings indicate that self-confidence, professional competence, and work motivation each have a positive and significant influence on employees’ affective commitment. Furthermore, these variables simultaneously contribute to strengthening affective commitment among public sector employees. Research Implications: The study contributes to the literature on organizational behavior and public sector management by highlighting the importance of strengthening employees’ self-confidence, professional competence, and work motivation in enhancing affective commitment. Practically, public organizations are encouraged to develop strategies and programs that support employee competence, motivation, and psychological readiness to improve organizational commitment and performance.